Language policies and portuguese language in Macau, China: an introduction - Teixeira-e-Silva, Roberval (2014)
his text is an introduction to a research that aims to understand the complexity of the language policies of Macau, especially in relation to the Portuguese  language. Thus underlines the geopolitical establishment of the Macau SAR, in terms of subjects and languages that constitute it, and highlights a specific political event – the Sino-Portuguese Joint Declaration of 1987 – as a framework for the construction of actions for managing languages in the territory. Also includes the recognition of a transnational status for the Portuguese language  and ends by suggesting the necessity for a reflection on the concept of language  and the urgency of adopting language policies that consider the Portuguese as a polycentric language and that recognize the territory as immersed in  globalization, multilingualism and super-diversity.